Probing plasmonic system by the simultaneous measurement of Raman and fluorescence signals of dye molecules - Dvoynenko, M.M.; Kazantseva, Z.I.; Strelchuk, V.V.; Kolomys, O.F.; Bortshagovsky, E.G.; Venger, E.F.; Tronc, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The simultaneous measurement of Raman and fluorescence signals was proposed to find out the molecule-metal distance. The ratio between Raman and fluorescence intensities was used to estimate molecule-metal distance in nanometer scale. A low-value intensity of the fluorescence of the dye molecules was found using the photobleaching effect. Made was a comparison of experimental results with a theoretical model, which showed well agreement.